Health challenges on research and cruise ship expeditions to Antarctica - Heggie, Travis; Küpper, Thomas (Health Promotion & Physical Activity, 2022)
Antarctica is one of the last great wilderness areas on Earth. Early Antarctic expeditions during the Heroic Age of Antarctic discovery (1895–1922) returned reports of frostbite, scurvy, snow blindness, and death. Today, over 50,000 people travel to the Antarctic each year via research expeditions, commercial cruise ships (tourism), and research cruises. This study reviewed the existing research reporting the health challenges encountered during modern day travel to Antarctica. The results identified a transition from the Heroic Age when death was common to a contemporary time when death is an uncommon event. The review identified musculoskeletal and soft tissue injuries resulting from moving equipment and supplies to be the most common health challenge encountered by long-term land expeditions. Digestive issues such as constipation and dyspepsia were also common in during the coldest months. For tourist oriented commercial cruise ships, motion sickness resulting from rough seas was most prominent. Specifically, the small nature of the cruise ships made them prone to rough seas in Drakes Passage. During scientific cruises where research is primarily conducted aboard the ship, dermatological conditions (viral, fungal, bacterial) such as dry skin, dry lips, eczema are the most common health challenge. Musculoskeletal and soft tissue injuries are also common given the physical challenge associated with strenuous research.